Neuroinflammation and the Immune-Kynurenine Pathway in Anxiety Disorders - Kim, Yong-Ku; Jeon, Sang W. (Current Neuropharmacology, 2018)
Background: Recently, neuroinflammation and the immune-kynurenine pathway have received increased attention in the psychoimmunology field of major depressive disorder (MDD), while studies related to anxiety disorders have been very limited. Objective: This study reviewed possible mechanisms by which stress or inflammation modulate anxiety through tryptophan metabolism and the kynurenine pathway. Methods: Relevant literature was identified through a search of MEDLINE via PubMed. Results: Accumulating evidence has indicated the modulatory effects of the immune-kynurenine pathway on anxiety. The tryptophan catabolites (TRYCATs) in the kynurenine pathway imbalanced by stress or inflammation induce serotonin and melatonin deficiency, making anxiety reactions more sensitive. In addition, TRYCATs cause or sustain anxiety by acting as endogenous anxiogens or anxiolytics, an NMDA agonist or antagonist, or a free radical generator. Conclusion: We hope that our understanding of the psychoimmunological mechanisms of anxiety will be expanded and anxiety-related studies will receive greater attention.
Keywords: Anxiety